IEEE P7001: A Proposed Standard on Transparency - Winfield, Alan F. T.; Booth, Serena; Dennis, Louise A.; Egawa, Takashi; Hastie, Helen; Jacobs, Naomi; Muttram, Roderick I.; Olszewska, Joanna I.; Rajabiyazdi, Fahimeh; Theodorou, Andreas; Underwood, Mark A.; Wortham, Robert H.; et al. (Frontiers in Robotics and AI, 2021)
This paper describes IEEE P7001, a new draft standard on transparency of autonomous systems1. In the paper, we outline the development and structure of the draft standard. We present the rationale for transparency as a measurable, testable property. We outline five stakeholder groups: users, the general public and bystanders, safety certification agencies, incident/accident investigators and lawyers/expert witnesses, and explain the thinking behind the normative definitions of “levels” of transparency for each stakeholder group in P7001. The paper illustrates the application of P7001 through worked examples of both specification and assessment of fictional autonomous systems.